2011
DOI: 10.1105/tpc.111.083634
|View full text |Cite
|
Sign up to set email alerts
|

DOLICHOL PHOSPHATE MANNOSE SYNTHASE1 Mediates the Biogenesis of Isoprenyl-Linked Glycans and Influences Development, Stress Response, and Ammonium Hypersensitivity in Arabidopsis  

Abstract: The most abundant posttranslational modification in nature is the attachment of preassembled high-mannose-type glycans, which determines the fate and localization of the modified protein and modulates the biological functions of glycosylphosphatidylinositol-anchored and N-glycosylated proteins. In eukaryotes, all mannose residues attached to glycoproteins from the luminal side of the endoplasmic reticulum (ER) derive from the polyprenyl monosaccharide carrier, dolichol P-mannose (Dol-P-Man), which is flipped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 128 publications
2
56
1
Order By: Relevance
“…Similarly, increased Dol-P-Man biosynthesis results in an increased resistance of DPMS1-OE plants to tunicamycin (Jadid et al, 2011). It seems worth mentioning that neither of the mutant lines characterized in this study, pprd2-1 +/2 and pprd2-2 +/2 , showed hypersensitivity to ammonium salts (mentioned earlier; Jadid et al, 2011). This discrepancy could result from differences in the experimental conditions used.…”
Section: Polyprenol Reductase: a Hitherto Uncharacterized Component Ocontrasting
confidence: 44%
See 2 more Smart Citations
“…Similarly, increased Dol-P-Man biosynthesis results in an increased resistance of DPMS1-OE plants to tunicamycin (Jadid et al, 2011). It seems worth mentioning that neither of the mutant lines characterized in this study, pprd2-1 +/2 and pprd2-2 +/2 , showed hypersensitivity to ammonium salts (mentioned earlier; Jadid et al, 2011). This discrepancy could result from differences in the experimental conditions used.…”
Section: Polyprenol Reductase: a Hitherto Uncharacterized Component Ocontrasting
confidence: 44%
“…Most probably an elevated Dol level compensates, at least partially, for the tunicamycin-induced disturbances in protein glycosylation, as clearly shown for pollen. Similarly, increased Dol-P-Man biosynthesis results in an increased resistance of DPMS1-OE plants to tunicamycin (Jadid et al, 2011). It seems worth mentioning that neither of the mutant lines characterized in this study, pprd2-1 +/2 and pprd2-2 +/2 , showed hypersensitivity to ammonium salts (mentioned earlier; Jadid et al, 2011).…”
Section: Polyprenol Reductase: a Hitherto Uncharacterized Component Omentioning
confidence: 86%
See 1 more Smart Citation
“…This phenomenon needs further studies of which identification and characterization of the polyprenol reductase(s) involved is the first indispensable step. The occurrence of a polyprenyl reductase (SRD5A3-like gene product) in Arabidopsis leaves has been reported recently [31] while its human counterpart had been characterized only one year earlier [22].…”
Section: Sugar Modulates Polyisoprenoid Composition and Content In Hamentioning
confidence: 99%
“…All of these molecules possess many biological functions, including photosynthesis, cellular respiration, phytohormones, phytoalexins and pollination attractors [4]. In addition, they also serve as a central component of the cell membrane [5] and involved in the posttranslational protein modification [6]. A recent study has also demonstrated that terpenoids-derived molecules regulate polar auxin transport which plays an essential role in plant development [7].…”
Section: Introductionmentioning
confidence: 99%